Characteristics of forage and feeding behavior of Nellore heifers fed hydrolyzed sugarcane - Missio, Regis Luis [UNESP]; Oliveira, Mauro Dal Secco de [UNESP]; Sforcini, Mariana Paula Rossi [UNESP]; Abud, Guilherme de Carvalho [UNESP]; Ferrari, Viviane Borba [UNESP]; Elejalde, Denise Adelaide Gomes; Ezequiel, Jane Maria Bertocco [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the chemical characteristics of the forage and ingestive behavior of Nellore heifers fed hydrolyzed sugarcane in different periods of storage. Twenty-four heifers with initial body weight of 119.6±8.1 kg were utilized. The experimental design was completely randomized, in which the treatments were diets with fresh sugarcane and hydrolyzed sugarcane (5 g of lime kg-1 of chopped sugarcane) stored for 24, 48 or 72 hours as the only roughage. The addition of lime to sugarcane associated with its storage up to 72 hours provided an increase of 20% of the potentially degradable cell wall of carbohydrates, from 382.4 to 458.8 g kg-1 of total carbohydrates. The in vitro digestibility of dry matter was altered by the storage of hydrolyzed sugarcane, increasing 7.08% when the storage time was increased from 24 to 72 hours. Heifers fed fresh sugarcane remained more time consuming compared with heifers fed other diets. The time used for water intake was not influenced by the diet. The rumination time presented a quadratic variation in relation to storage time of the hydrolyzed sugarcane, with higher values for the of hydrolyzed sugarcane diets stored for 48 hours. Heifers fed hydrolyzed sugarcane spent more time on other activities than those fed fresh sugarcane. The supply of hydrolyzed sugarcane stored up to 72 hours in the proportion of 600 g kg-1 of dry matter in the diet, alters the intake patterns, reducing the feed intake in Nellore heifers.
Keywords: Digestibility; hydrated lime; Idle; nonstructural carbohydrates; Rumination